2014
DOI: 10.1074/mcp.m113.029793
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Chemical Proteomics Approach to Profile the Specific Cellular Targets of Andrographolide, a Promising Anticancer Agent That Suppresses Tumor Metastasis

Abstract: Drug target identification is a critical step toward understanding the mechanism of action of a drug, which can help one improve the drug's current therapeutic regime and expand the drug's therapeutic potential. However, current in vitro affinity-chromatography-based and in vivo activity-based protein profiling approaches generally face difficulties in discriminating specific drug targets from nonspecific ones. Here we describe a novel approach combining isobaric tags for relative and absolute quantitation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 53 publications
2
82
0
Order By: Relevance
“…Andrographolide is best known for its anti-inflammatory activity as an NF-kB inhibitor. It binds specifically to the DNA binding subunit p50 at Cys 62 residue of the NF-kB complex, preventing the complex from binding to DNA for gene transcription (39). It has been shown that andrographolide suppressed LPS-induced p65 phosphorylation, p65 nuclear translocation, and NF-kB DNA binding activity in mouse MEL-12 epithelial cells and Raw 264.7 cells (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide is best known for its anti-inflammatory activity as an NF-kB inhibitor. It binds specifically to the DNA binding subunit p50 at Cys 62 residue of the NF-kB complex, preventing the complex from binding to DNA for gene transcription (39). It has been shown that andrographolide suppressed LPS-induced p65 phosphorylation, p65 nuclear translocation, and NF-kB DNA binding activity in mouse MEL-12 epithelial cells and Raw 264.7 cells (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…9 Andrographolide (AG; Figure 1) is a natural diterpenoid isolated from Andrographis paniculata, which is a traditional remedy for fever, cold, sore throat, and various chronic infectious diseases. [10][11][12] Moreover, previous studies have shown that AG possesses many pharmacological activities, including anti-inflammatory, 13 antioxidative, 14 and anticancer 15 activities. A previous study showed that pretreatment with the ethanolic extract of A. paniculata provided significant protection against gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…An iTRAQ quantitative proteomics approach was used in tandem with BONCAT to differentiate any potential background contamination from selective enrichment, 29,30 to enhance the reliability of the results obtained. The background contamination includes the pre-existing proteins nonspecifically binding to the beads, as well as the endogenously biotinylated proteins, since streptavidin beads were used for the protein enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…The iTRAQ labeling technique 29,30,48 was employed to investigate the changes in the proteomic profiles upon autophagy induction, per the manufacturer's instructions with minor modifications. Briefly, the dried digested peptides were resuspended in equal amounts of dissolution buffer (0.5 M TEAB; Sigma-Aldrich, T7408).…”
Section: Isobaric Tag For Relative and Absolute Quantification (Itraqmentioning
confidence: 99%
See 1 more Smart Citation